Physical quality of bauxite tailing after a decade of environmental recovery - Guimarães, Lorena Abdalla; Dias, Luiz; Rocha, Genelício; Assis, Igor; Fernandes, Raphael (Revista Ciência Agronômica, 2018)
Tailings from bauxite washing produced in Porto Trombetas, Pará state, a Brazilian Amazon region, have chemical and physical characteristics limiting the development of plants, which hinders to revegetate the tanks where they are deposited. This study was carried out under field conditions, and aimed to assess the physical quality of these tailings after a decade of recovery practices. Three treatments were assessed: no application of inputs and planting of seedlings (T1) and two levels of fertilization, one with lower (T2) and other with higher (T3) doses of limestone and fertilizers associated with planting tree seedlings. After ten years of experimentation, penetration resistance (PR) and substrate moisture up to 60 cm depth were assessed and the least limiting water range (LLWR), water retention curve (WRC), and pore size distribution were determined and calculated. After a decade of environmental recovery, differences in physical characteristics were observed in the tailings due to different revegetation modes. Moisture in the substrate profile, LLWR, WRC, and pore size distribution were sensitive indicators to variations in substrate physical quality. Liming, fertilization, and planting of seedlings are necessary for revegetation and improvement of the physical quality of tailings. Treatment T3 was the best intervention identified so far for tank revegetation. The absence of fertilization and planting precludes revegetation even with sources of propagules nearby.